Efektivitas dan Waktu Tunggu Kapal: sebagai Bukti Empiris Kinerja dan Produktivitas Bongkar Muat pada Pelabuhan Saketa-Halmahera - Berliana, Dhana; Maemunah, Siti; Ricardianto, Prasadja; Agusinta, Lira; Saribanon, Euis (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to examine the influence of time effectiveness and vessel waiting time on loading and unloading productivity through the performance of stevedoring activities at Saketa Port. This research is essential to provide deeper insights into formulating more effective strategies to improve operational efficiency at the port, thereby contributing to regional economic growth. A quantitative approach was employed, with data collected through questionnaires and interviews involving the entire population of 97 respondents. These respondents included port operators, vessel crew, cargo owners, and stevedoring laborers. Data analysis was conducted using Structural Equation Modeling (SEM). The findings indicate that time effectiveness has a positive and significant influence on both loading and unloading productivity and performance. Conversely, vessel waiting time shows a positive influence on performance but does not significantly affect productivity. Furthermore, loading and unloading performance does not significantly influence productivity directly. The study also reveals that neither time effectiveness nor vessel waiting time has an indirect effect on productivity through performance. These results highlight the critical role of effective time management in stevedoring activities to enhance port productivity. Additionally, they underline the need for operational strategies focused on reducing vessel waiting times and improving technical performance.